The impact of consumer positive personality on the purchase behavior of smart products - Li, Dan; Yu, Dengke (Frontiers in Psychology, 2022)
While the consumption of smart products is continuously increasing, it is essential to explore the trigger mechanism of consumer behavior in respect of smart products purchase. In this scenario, we aims to investigate the impact of consumer’s positive personality on the purchase behavior. We constructed a structural equation model based on partial least square method and tested our hypotheses on basis of data analysis. The data was collected by a survey of 326 Chinese consumers. We found two affecting paths from consumer’s positive personality to smart products purchase. First, consumer knowledge promoted by positive personality raises purchase intention and in turn stimulates purchase behavior. Second, consumer’s positive personality improves perceived income, which determines actual purchase behavior. The study deepens our understanding of the trigger mechanism of smart products purchase behavior and enriches consumer behavior theory.